Facing Challenges of Covid-19: The Perspective of China and Ethiopia Educational Institutions - Chen Chang; Getaye Aytenew (JETL (Journal of Education, Teaching and Learning), 2021)
Concerning the fast spread of COVID-19, countries all over the world have closed academic institutions to stop the pandemic. It is now apparent that students and teachers require other options that have to be more versatile, easily accessible, and support the current technologies and conditions to face the unpredictable future. From the review, literature disclosed that universities throughout the globe are establishing and implementing electronics learning platforms as a basic need in academic institutions. This manuscript aimed to assess the status of electronics learning in China and Ethiopian educational institutions to counter the challenges of the closure of schools because of the outbreak of the pandemic. The paper highlights concerning e-learning in the sense of China and Ethiopia, e-learning challenges, and successful experiences. This review paper also suggests educators use e-learning and distance learning as a necessity to advance learning, particularly during this pandemic season.